KESANGGUPAN PEMIMPIN MEMBANGUN RUH AL-JAMA’AH DALAM SISTEM MANAJEMEN PENDIDIKAN ISLAM - Khardi, Syarifuddin; Syukri, Ahmad; Us, Kasful Anwar (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2019)
Leaders in an Islamic education management system have a very important role. An organization will run well is greatly influenced by the spirit of leadership. In education management in general there are a number of types of leadership with different game strategies. Sometimes you have to place and apply it in its place. Leadership in Islam provides a very detailed picture of how to build a spirit of leadership. Not only outwardly but how to build the spirit of al-Jama'ah that well, so that leadership in the Islamic education management system has a sharp influence on Jamaahah. So basically the initial foundation of a leader is to build a jama'ah spirit first. Keywords. System, Leader, Islamic Education Management